The Design of Terrestrial Trunked Radio (TETRA) Communication System at Juanda Airport - Miasari, Devi; Wijayanti, Ari; Puspitorini, Okkie (Politeknik Elektronika Negeri Surabaya (PENS), 2013)
Nowdays the application of wireless communication system at the airport area is very important as it is used to support the services and savety of people. In the beginning the communication is done by using Handy Talkie (HT) and the communication is limited on voice. To increase the working operation and savety of public the data communication, besides the voice, is needed. This research is designed to use wireless communication using TETRA technology on frequency 450 MHz by counting the linkbudget and are coverage of the airport. The calculation shows that the more the distance between Tx and Rx, the bigger the pathloss will be. When the distance is 5 km, the pathloss reaches 144,46dBm on the antenna receiver 1,25m. Menwhile the Rx heigh antenna does not have any significance effect on the pathloss. The coverage area for the plan can reach the distance 3,3 km when the power of transmission is 33 dBm which is enough to cover the whole area of the airport.Keywords: TETRA, Link Budget, Pathloss, Airport